1999
DOI: 10.1046/j.1365-3016.1999.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

A history of placental dysfunction and risk of placental abruption

Abstract: In a population-based historic cohort study, we assessed the possible association of fetal growth retardation, preterm birth and pregnancy-induced hypertension in the immediately preceding pregnancy with placental abruption in the current pregnancy, which would suggest a shared aetiological factor. We also assessed whether chronic hypertension, diabetes mellitus and a history of Caesarean section are associated with placental abruption. Preterm birth and small-for-gestational-age (SGA) in the immediately prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 37 publications
(55 reference statements)
4
69
2
7
Order By: Relevance
“…Furthermore, previous caesarean delivery is also known to be associated with an increased risk of abnormal placentation leading to abruption, placenta praevia, and morbid adherence of the placenta. [8][9][10] Stillbirth is associated with a high resistance pattern of uterine artery and umbilical artery blood flow, which may indicate maldevelopment of the villous tree. [32][33][34] The association between previous caesarean and stillbirth might be, therefore, another manifestation of abnormal placentation caused by a uterine scar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous caesarean delivery is also known to be associated with an increased risk of abnormal placentation leading to abruption, placenta praevia, and morbid adherence of the placenta. [8][9][10] Stillbirth is associated with a high resistance pattern of uterine artery and umbilical artery blood flow, which may indicate maldevelopment of the villous tree. [32][33][34] The association between previous caesarean and stillbirth might be, therefore, another manifestation of abnormal placentation caused by a uterine scar.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, it has also been noted that placental complications, such as abruption and placenta praevia, are more common in women who have previously undergone caesarean section, 8,9 and the association with abruption has been observed in women with no previous history of abruption and is independent of obvious confounders. 10 The effect of previous caesarean delivery on the risk of antepartum perinatal death in subsequent pregnancies is not known. We did a large-scale, retrospective, cohort study to establish whether caesarean delivery in a first pregnancy was associated with an increased risk of antepartum stillbirth in the second.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a history of placental dysfunction, identified by previous small for gestational age or preterm birth, is associated with an increased risk of placental abruption. 13 Similarly, a pregnancy following placental abruption has an increased risk of recurrence, with an excess risk of small for gestational age, preterm birth. 14 Placentas of thrombophilic women have been characterized by an increased rate of vascular damage, multiple infarcts and fibrinoid necrosis.…”
Section: Commentmentioning
confidence: 99%
“…It was to become 336 millions by 2030 [2]. Chronic hypertension and diabetes mellitus may cause or aggravate such dysfunction thus causing placental abruption [3]. Placenta is the organ within the uterus by means of which the embryo is attached to the wall of the uterus.…”
Section: Introductionmentioning
confidence: 99%